Inflammatory Cell‐Inspired Cascade Nanozyme Induces Intracellular Radical Storm for Enhanced Anticancer Therapy. Issue 3 (6th January 2023) - Liu, Xun; Li, Wei; Wang, Mengru; Liu, Ningyu; Yang, Qiang; He, Yunjie; Hu, Duanmin; Zhu, Rongying; Yin, Lichen
Abstract: Manipulating intracellular levels of reactive oxygen and nitrogen species (RONS) is of great potential for cancer treatment. Inspired by the natural mechanism of a radical storm in inflammatory cells via activated and regulatable biocatalysis, the authors herein report a self‐powered nanozyme that can enable RONS production in tumor cells via cascade reactions. The nanozymes are constructed via glucose oxidase (GOx)‐templated inverse microemulsion polymerization from acrylamide, arginine‐acrylamide, ferrocene‐acrylate, and N, N′ ‐bis(acryloyl)cystamine, followed by surface coating with hyaluronic acid. After targeted delivery into cancer cells, the nanozymes are dissociated by intracellular glutathione to release GOx, which decomposed glucose to generate gluconic acid and H2 O2 . Under such acidified conditions, H2 O2 efficiently oxidized pendant arginine residues to produce nitric oxide, transformed into a highly toxic hydroxyl radical and superoxide anion via ferrocene‐mediated Fenton reaction and Haber–Weiss cycle, and simultaneously generated peroxynitrite anion via reaction between NO and ·O2 −, thus provoking the RONS radical storm to effectively eradicate A549 tumor cells both in vitro and in vivo. This nature‐inspired enzyme‐chemical dynamic therapy may provide a promising modality for anti‐cancer treatment. Abstract : Glucose oxidase‐templated nanozyme prepared via inverse microemulsion polymerization is designed to induce intracellular radical storm for enhanced anticancer therapy. Upon targeted internalization into tumor cells, the nanozyme triggers cascaded reactions including reduction‐responsive nanozyme dissociation, GOx‐catalyzed H2 O2 /H + production, and arginine‐ and ferrocene‐mediated reactive oxygen and nitrogen species generation, thus provoking pronounced anticancer efficacy.